Efavirenz-induced grade III gynecomastia in an HIV-positive male patient: a case report and literature review - Zhou, Lu; Luo, Yunhao; Liao, Weiwei; Yang, Delin; Hu, Wen (Frontiers in Medicine, 2025)
BackgroundEfavirenz, a non-nucleoside reverse transcriptase inhibitor, is a preferred drug for the treatment of HIV-positive patients. However, one of its adverse effects is gynecomastia, which not only causes psychological distress to patients, affecting their daily lives and work, but also may undermine their treatment adherence. Although numerous studies have documented cases of gynecomastia in HIV-positive patients after antiretroviral therapy (ART), severe cases of gynecomastia are rarely reported.Patient presentationA 29-year-old male patient initiated a triple therapy regimen of efavirenz, lamivudine, and tenofovir disoproxil fumarate after being diagnosed with HIV. Two years later, he experienced progressive enlargement of the bilateral breasts but did not report the symptoms to his physician. After 6 years of ART, the patient developed grade III gynecomastia in both breasts, accompanied by significant psychological distress, prompting a visit to the breast surgery department. After excluding other potential drug adverse effects or underlying diseases, the patient’s gynecomastia was attributed to efavirenz. Owing to severe enlargement of the breasts, the patient underwent bilateral mastectomy, successfully recovered and was discharged from the hospital. Postoperative follow-up revealed significant improvement in the patient’s anxiety and depressive symptoms.ConclusionGynecomastia represents a nonnegligible adverse effect of efavirenz that clinicians must recognize and manage promptly. Prior to initiating efavirenz therapy, it is imperative to thoroughly inform patients about potential adverse reactions, emphasizing the importance of seeking medical attention promptly should any side effects arise. Early detection and management of gynecomastia can mitigate its psychological impact and ensure continued adherence to ART.